Advancing university management during the pandemic of COVID-19 at ESPOCH - Byron Vaca; Magdy Echeverría; Rafael Córdova (Universitas Diponegoro, 2022)
The university action to the issues that came along with COVID-19 needed to embrace the whole management system for facing the challenges related to infrastructure, water, waste management, transport, and education. Escuela Superior Politécnica de Chimborazo (ESPOCH) has focused most of its efforts into building and maintaining its infrastructure. The linkage to society has become of paramount importance for ESPOCH, during this time, the university becoming the first and biggest vaccination site in the city. Moreover, several conferences related to training and business ideas for entrepreneurs have been launched, always keeping sustainability in mind. Universal access for people with disabilities and the use of efficient lightning is a common characteristic of all the new buildings; the residues are technically disposed of having managed 4413 m3 of them during 2020. The same technical disposal of residues is applied for recyclable, biodegradable, dangerous and inert ones. Additionally, the campus green areas have been maintained and forested using native species planting about 500 new trees during the last year. The opportunities brought by the pandemic have been harnessed to strengthen the setting and infrastructure of ESPOCH while at the same time serving the surrounding community.Keyword: university management, COVID-19, Latin America, sustainability, higher education.